A parametric study on strawberry radiated shaped monopole antenna for ultrawide-band applications - Al-Gburi, Ahmed Jamal Abdullah; Zakaria, Zahriladha; Ibrahim, Imran Mohd; Akbar, Muhammad Firdaus; Al-Obaidi, Aymen Dheyaa Khaleel; Khabba, Asma (Institute of Advanced Engineering and Science, 2023)
This article gives a parametric study on strawberry-shaped monopole antennas for ultra-wideband (UWB) systems. The antenna design consisted of three different parametric design steps to structure the strawberry radiated monopole antenna. The scheduled strawberry monopole antenna was simulated on an FR4 substrate in a low profile for UWB applications. The total physical dimension is 26 mm×26 mm×1.6 mm, corresponding to the centre frequency of 7.5 GHz. The strawberry antenna is fed via a coplanar waveguide (CPW) to attain the best impedance matching for UWB systems. The presented monopole antenna has an impedance UWB bandwidth of 11.0 GHz from 2.6 GHz up to 13.6 GHz at −10 dB return loss. The simulated UWB strawberry monopole antenna displays an omnidirectional radiation behaviour with a simulated gain of 7.3 dB at 13.6 GHz, a directivity of 7.5 dBi at 13.6 GHz and favourable radiation efficiency of 97%. The proposed monopole UWB strawberry antenna has the technological possibility to be used for UWB applications.